A multi-centre study of the effects of direct observation of hand hygiene practices on alcohol-based handrub consumption. Issue 4 (December 2022) - Fujita, Retsu; Arbogast, James W.; Yoshida, Rika; Hori, Satoshi
Summary: Introduction: The World Health Organization recommends monitoring alcohol-based handrub (ABHR) consumption and direct observation of hand hygiene practices to ensure compliance. In Japan monitoring of ABHR consumption is widely performed. However, direct observation is not common, particularly in small facilities and non-acute-care facilities. Hence, the current study aimed to evaluate the longitudinal effects of direct observation of hand hygiene practices and monitoring of ABHR consumption with provision of feedback to healthcare personnel on ABHR consumption and hand hygiene compliance. Methods: We conducted a 4-year prospective intervention study. Monitoring of ABHR consumption and direct observation of hand hygiene practices with monthly feedback to healthcare personnel was implemented in 17 facilities. These consisted of 11 acute-care facilities of varying sizes and six non-acute-care facilities. A generalized linear mixed model analysis was performed to assess factors associated with ABHR consumption. Results: All facilities implemented ABHR consumption monitoring within one month of starting the study. However, the mean time required to implement direct observation of hand hygiene practices was 24.7 (±19.1) months. The ABHR consumption increased significantly ( P <0.0001) in all medical facilities after implementing the direct observation. Multivariable regression analysis showed the hospital ward type, duration of ABHR consumption monitoring, and duration of direct observation of hand hygiene practices were independently associated with ABHR consumption. Conclusions: Direct observation of hand hygiene practices with feedback should be implemented more widely in combination with ABHR consumption monitoring to help increase hand hygiene compliance.